2016
DOI: 10.5505/tjtes.2016.26053
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Cholecystostomy: A Curative Treatment Modality In Elderly & High ASA Score Acute Cholecystitis Patients.

Abstract: BACKGROUND: Acute cholecystitis (AC) is a common emergency seen by general surgeons. Optimal treatment is laparoscopic cholecystectomy (LC); however, in cases where surgery cannot be performed due to high risk of morbidity and mortality, such as in elderly patients with comorbid diseases, other treatment modalities may be used. Percutaneous cholecystostomy (PC) is one alternative method to treat AC. PC can be used to provide drainage of the gall bladder and control infection. Subsequently, interval cholecystec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…The reported incidence of PC-related complications varies from 2.5 to 69% (15, 20,25,38,49,[66][67][68]. Among all the complications, dislodgement of the cholecystostomy tube is the most common occurrence, which can account for more than half of all events in some publications (20,27,38,66,68).…”
Section: Pc-associated Complications and Care Complicationsmentioning
confidence: 99%
“…The reported incidence of PC-related complications varies from 2.5 to 69% (15, 20,25,38,49,[66][67][68]. Among all the complications, dislodgement of the cholecystostomy tube is the most common occurrence, which can account for more than half of all events in some publications (20,27,38,66,68).…”
Section: Pc-associated Complications and Care Complicationsmentioning
confidence: 99%
“…Percutaneous cholecystostomy is a safe and effective way to manage acute cholecystitis in patients unsuitable for surgery. 1 The incidence of cholecystocutaneous fistulas is low, and most form spontaneously due to untreated cholecystitis or are associated with malignancy of the gallbladder. 2 , 3 An alternative management option for patients who are not suitable for surgery is to use endoscopic gallbladder drainage with a lumen-apposing metal stent (LAMS).…”
Section: Case Reportmentioning
confidence: 99%
“…Of these, 22 studies reported on outcomes following early interval LC 7,[15][16][17][18][19][20][21][22][23][24][25]36,[43][44][45]47,[49][50][51][52][53] , and 22 studies following late interval LC 3,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]45,46,48 . Three studies reported and compared outcomes in both groups 25,36,45 .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…There were 4 studies that did not report any morbidity outcomes 31,39,40,52 . In the remaining 37 studies, the overall reported 90-day morbidity was 268 out of 2028 (13.2%) patients in the early interval LC group and 236 out of 1772 (18.4%) patients in the late J o u r n a l P r e -p r o o f interval LC group.…”
Section: Morbidity and Mortalitymentioning
confidence: 99%